A CORRELATION OF PRE-OPERATIVE LYMPHOCYTES AND MONOCYTES RATIO WITH PROGNOSIS PATIENTS WITH OSTEOSARCOMA - David M Purba; C Siregar; ID Winanto (poltekkes kemenkes mataram, 2017)
The pathogenesis cancer is affected by immune system and inflammation. In some neoplasm, the infiltration of mononuclear cells is an indicator of an excellent prognosis. An experimental trial proved that cytotoxic T cells (CTL) produce an effective antitumor immune response in vitro. The monocytes that enter the tissues (macrophages) produce TNF α which increases the ability of the invasion, angiogenesis and cancer cell motility. The purpose of this study was to investigate the ratio of lymphocyte monocyte as a predictor of osteosarcoma prognosis. The research was an analytical retrospective and data collection obtained from patients’ medical records that have been diagnosed as Osteosarcoma at Haji Adam Malik Hospital in Medan. From 2011 to 2016, we obtained 41 patients who met the inclusion criteria. The ratio of lymphocyte-monocyte (LMR) derived from pre-surgery blood test. LMR cut-off value was determined by ROC curve and the Overall Survival was taken from surgery until the patients died. The mean age of the subjects is 22.41 ±13.79 with 28 (68.3%) males, most of the tumours were located in the femur (52%) and as many as 36 patients died (87.8%). The LMR cut off obtained from the ROC curve was 2.34. There were 23 patients (56.1%) with LLMR. Bivariate analysis using chi-square test indicated no visible relationship between the pre operation LMR with the osteosarcoma prognosis (p = 0.083). Kaplan Meier curve showed in HLMR, one year and two year survival were 0.5 and 0.38, respectively, whereas in LLMR, one year and two years survival were 0.38 and 0.08, respectively. The conclusion: There is no relationship between pre operation LMR with the prognosis of patients with osteosarcoma (p = 0.083) but the Kaplan Meier curve showed the overall survival of HLMR are better than the LLMR.